Assessment of glyphosate and its metabolites’ residue concentrations in cultured African Catfish offered for sale in selected markets in Ibadan, Oyo State, Nigeria - Alarape, Selim Adewale; Fagbohun, Adekemi Florence; Ipadeola, Oladeni Adegoke; Adeigbo, Anthony Ayodeji; Adesola, Ridwan Olamilekan; Adeyemo, Olanike Kudirat (Frontiers in Toxicology, 2023)
Introduction: Glyphosate is a non-targeted organophosphate insecticide whose solubility and mobility in hydrophilic solvents enable its rapid leaching into the soil and subsequent contamination of ground and surface water and possible build-up in the aquatic food chain. Based on the public health importance of glyphosate in fish through consumption, it is crucial to determine the current residue concentration in culture Clarias gariepinus species. The aim of the present study is to evaluate glyphosate’s residue concentrations and its metabolites in cultured African Catfish offered for sale in selected markets in Ibadan. Methods: A total of twenty-five (25) adult Clarias gariepinus (300 ± 50 g) were sourced from five (5) selected active fish markets (Ojoo, Iwo road, Eleyele, Challenge, and Apata) within the Ibadan metropolis. The collected fish tissue samples (liver, kidney, and spleen) were prepared for glyphosate residue concentration analysis using Liquid Chromatography (LC). Results: The results showed that glyphosate residues were recorded in all the seventy-five (75) fish tissue samples obtained from the selected fish markets in the Ibadan metropolis and all residue concentrations were above both the recommended Acceptable Daily Intake (ADI) of 1.0 mg/kg (1 × 10−3 mg/L) and Maximum Residue Limits (MRL) of 0.01 mg/kg (1 × 10−5 mg/L). Isopropylamine has the highest residue concentration followed by N-Phosphonomethyl and Aminomethylphosphonic Acid (AMPA), while N-Acetyl Glyphosate has the least residue concentration across the sampled markets. Discussion: The presence of residues of glyphosate and its metabolites in ready-to-eat fish calls for holistic, systematic, and effective risk management strategies towards monitoring pesticide/herbicide usage in aquaculture production and ensuring the provision of wholesome fish and fish products for the consumers.